The costs of consumption smoothing: less schooling and less nutrition. (September 2019) - De Magalhães, Leandro; Koh, Dongya; Santaeulàlia-Llopis, Räul
Abstract: Using novel microdata, we explore lifecycle consumption in Sub-Saharan Africa. We find that households' ability to smooth consumption over the lifecycle is large, particularly, in rural areas. Consumption in old age is sustained by shifting to self-farmed staple food, as opposed to traditional savings mechanisms or food gifts. This smoothing strategy indicates two important costs. The first cost is a loss of human capital as children seem to be diverted away from school and into producing self-farmed food. Second, a diet largely concentrated in staple food (e.g., maize in Malawi) in old age results in a loss of nutritional quality for households headed by the elderly.